(untitled) (Research, Society and Development, 2024)
This article aims to evaluate the impact and benefit of Continuous Glucose Monitors (CGMs), specifically the FreeStyle Libre system, on the quality of life of patients with Type 2 Diabetes (T2DM), comparing the effectiveness of CGM with traditional glucose monitoring methods, like Self-monitoring Blood Glucose (SMBG) with capillary, focusing on reducing glycated hemoglobin (HbA1c) levels and reducing acute and chronic complications. The methodology used is based on a literature review with analysis of data obtained from studies and clinical trials available in the PubMed and EBSCO databases, examining the effects of CGM devices in reducing HbA1c, hypoglycemic events and vascular complications. The results indicate that the use of CGMs, such as the FreeStyle Libre, provides a significant reduction in HbA1c levels and a decrease in hypoglycemic episodes compared to traditional monitoring. Furthermore, CGM devices have been shown to be more effective in improving patients’ quality of life. It is concluded that, although CGMs have a higher initial cost, they are a cost-effective option in the long term due to the reduction of severe complications and associated costs. The incorporation of CGMs in the management of type 2 diabetes is recommended to optimize glycemic control and improve patient well-being.